Patterns and pseudo-randomness using complex systems - Machicao, Jeaneth; Bruno, Odemir M. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2018: Anais Estendidos do XVIII Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2018)
In this thesis, we developed a method that exploits the random-like properties of chaotic systems as a pseudo-random number generator (PRNG). We explored the k-digits to the right of the decimal separator (less significant digits) of an original orbit of a chaotic map. This approach called as “deep-zoom” demonstrated the relationship between the parameter k and the quality of the pseudo-random sequences, since it showed a rapid transition from “weak to strong” randomness as k tends to infinity, thus allowing to manipulate pseudo-randomness in a parametrically manner.